If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4ln(x + 2) + 3ln(4x + 9) = 0 Reorder the terms: 4ln(2 + x) + 3ln(4x + 9) = 0 (2 * 4ln + x * 4ln) + 3ln(4x + 9) = 0 (8ln + 4lnx) + 3ln(4x + 9) = 0 Reorder the terms: 8ln + 4lnx + 3ln(9 + 4x) = 0 8ln + 4lnx + (9 * 3ln + 4x * 3ln) = 0 8ln + 4lnx + (27ln + 12lnx) = 0 Reorder the terms: 8ln + 27ln + 4lnx + 12lnx = 0 Combine like terms: 8ln + 27ln = 35ln 35ln + 4lnx + 12lnx = 0 Combine like terms: 4lnx + 12lnx = 16lnx 35ln + 16lnx = 0 Solving 35ln + 16lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(35 + 16x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(35 + 16x)' equal to zero and attempt to solve: Simplifying 35 + 16x = 0 Solving 35 + 16x = 0 Move all terms containing l to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 16x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 16x = 0 + -35 16x = 0 + -35 Combine like terms: 0 + -35 = -35 16x = -35 Add '-16x' to each side of the equation. 16x + -16x = -35 + -16x Combine like terms: 16x + -16x = 0 0 = -35 + -16x Simplifying 0 = -35 + -16x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4[2(x-3)]= | | 7y+y(6-8)= | | 3x+x=1.35 | | 40-n=4n+7 | | 3x+x=135 | | 7(x-1)=6x+1 | | X^2-13x+60=90 | | 88=2+2(8-5x) | | 8x+6=5x+5 | | g-4=-3 | | 22=x^2 | | (-x^5/2)^4 | | m-9=3 | | y=1.2+0.8(-2) | | ln(x)+ln(5x)=9 | | -89=x+75 | | 9y-5y(6-8)= | | 12+6(z+2)=5z+2 | | pt+51=76 | | 7y+y(2-8)= | | 6-4x^5=4-3x^2 | | (6+x)(x)=28 | | 6-4x*5=4-3x*2 | | h+9=-45 | | 6+x(x)=28 | | -16t^2-120t+500=700 | | -19n+16=-18n-5 | | 43x=86 | | -19n+16=-18-5 | | 24+10x-x^2=p-(x-5)2 | | 15+6y=15y-3 | | 7x-25=-10 |